A micromechanics model for partial freezing in porous media. (1st December 2015) - Yang, Rongwei; Lemarchand, Eric; Fen-Chong, Teddy; Azouni, Aza
Highlights: The unfrozen water film is introduced in the micromechanics model. The initial stress and disjoining pressure are introduced in the model. The differences between the poromechanics and micromechanics model are discussed. The disjoining pressure becomes more and more significant when the freezing temperature decreases. The model results agree reasonably well with experimental results of cement-based materials. Abstract: Based on the local physical characterization of partial freezing in porous media, the role of the unfrozen water film, located between the in-pore ice crystal and pore wall, is paid special attention to in this study. The disjoining pressure within unfrozen water film, the membrane stress induced by surface tension effect, the thermal stress and the initial stress are fully accounted for in the proposed micromechanics model. The micromechanics model improves the physical understanding of the macroscopic mechanical behaviors of the partially frozen porous media. The micromechanics model is applied to simulate the free swelling of a undrained cement paste (denoted by CP) and an air-entrained mortar (denoted by AM). The model results are comparable with the experimental results on cement paste. The reasons for the discrepancies between the model results and experimental results on cement paste may lie in the overestimation of the ice content, which here is estimated by the pore size distribution by mercury intrusion porosimetry (MIP) and Gibbs–Thomson equation. However, the model results agree well with the experimental results of the air-entrained mortar, the ice content of which is determined by the differential scanning calorimeter (DSC). The disjoining pressure within partially frozen porous media will become more and more significant with decreasing temperature.